PENERAPAN METODE PROTOTYPE DALAM PERANCANGAN APLIKASI E-LAPOR BENCANA BPBD SUMEDANG BERBASIS ANDROID (P3M Politeknik Negeri Cilacap, 2019)
The disaster that occurred in Sumedang district was the main concern of the services provided by the BPBD of Sumedang Regency, the handling of disasters that was fast and precise became the motto of BPBD. But in practice there are many obstacles, one of which is the lack of community participation in disaster reporting and many other technical constraints. Whereas with this reporting BPBD can quickly and responsively handle the disaster. E-disaster report based on Android BPBD Sumedang district is present as an electronic disaster reporting service to overcome problems in the BPBD of Sumedang district. This e-disaster report was built using a prototype software design methodology. This methodology is very suitable for software that continues to grow such as Android-based software. With this disaster report, people can easily report disasters. The location of the disaster can also be detected with the GPS feature on the Android smartphone. The community only needs to attach a photo of the event and the description of the incident and the report will be processed immediately by the investigating officer. With this application, Sumedang District people can participate in disaster reporting, and the BPBD of Sumedang District can be helped in carrying out the handling and handling of disasters quickly and precisely in Sumedang District.